Bridging the constitutional divide : inside the White House Office of Legislative Affairs - Riley, Russell L. (Russell Lynn), 1958- (Presidency and leadership (Unnumbered), 2010)
Bridging the Constitutional Divide: Inside the White House Office of Legislative Affairs is sure to fascinate, and even to entertain, scholars, students, and general readers interested in the ever-shifting relationship of the presidency to the legislative branch.